2017
DOI: 10.4172/2168-9547.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence and Molecular Detection of Brucellosis among Febrile Patients in West Darfur State, Sudan

Abstract: Brucellosis is a worldwide zoonosis with a high degree of morbidity in humans. It was formerly known as Mediterranean fever, Malta fever or undulant fever. The aim of this study to determine the prevalence of brucellosis among febrile negative malaria patients consume raw milk in West Darfur State, Sudan. In this cross sectional study, one hundred and half blood samples were collected from febrile patients and examined by Rose Bengal (RBPT), ELISA, SAT and PCR methods. The results showed 55 samples were positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…countries. The RBT is an affordable, simple, sensitive and easiest methods to apply and the most globally used for recognizing antibodies of human brucellosis [29,30] In the work at hand, two hundred and eighty 280 (146 males and 134 female) blood samples were collected among Erbil Governorate, during the period from July 2017 to December 2017. The overall prevalence of brucella antibodies in blood from all collected human samples were 24 / 280 (8.6%), as shown in (Table 1), which is approach or slightly lower percentage with [31] in Pakistan whom found that the prevalence of Brucella infection was (9.33%) according to RBT, while [32] in Egypt reported that the prevalence of Brucella infection was (11.1%) according to RBT.…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
“…countries. The RBT is an affordable, simple, sensitive and easiest methods to apply and the most globally used for recognizing antibodies of human brucellosis [29,30] In the work at hand, two hundred and eighty 280 (146 males and 134 female) blood samples were collected among Erbil Governorate, during the period from July 2017 to December 2017. The overall prevalence of brucella antibodies in blood from all collected human samples were 24 / 280 (8.6%), as shown in (Table 1), which is approach or slightly lower percentage with [31] in Pakistan whom found that the prevalence of Brucella infection was (9.33%) according to RBT, while [32] in Egypt reported that the prevalence of Brucella infection was (11.1%) according to RBT.…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%
“…Human Brucellosis is a debilitating illness characterized by fever (78%), arthralgia (65%), myalgia (47%),and back pain (45%). Hepatomegaly (23%), spleenomegaly (26%) 11 . Human Brucellosis is often misdiagnosed or under diagnosed due to overlapping clinical manifestations with many other bacterial infections.…”
Section: Introductionmentioning
confidence: 99%